On possibility of pressure perturbation resonant excitation by an external low frequency helical field near edge plasma - Pankratov, I.M.; Omelchenko, A.Ya. (Вопросы атомной науки и техники, 2011)
In the frame of one-fluid MHD a possibility of the pressure perturbation resonant excitation by external low frequency helical magnetic perturbations near the plasma edge is shown. The plasma rotation plays the key role in this phenomenon. The plasma response has being taken into account. These pressure perturbations may affect on the ballooning and peeling modes stability.